PENGARUH CITRA MERK DAN KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN PADA CAFE AYAH BUNDA SITUBONDO DENGAN MINAT BELI KONSUMEN SEBAGAI VARIABEL INTERVENING - Basori, Noval; Kusnadi, Edy; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2022)
ABSTRACT Marketing is generally seen as the activity of creating, introducing, and handing over goods and services to consumers. Marketing is the process by which a company creates value for customers and the construction of strong customers to capture value from customers in return marketing is a function of the organization and a series of processes to create, communicating, and providing value to customers and managing customer relationships in a way that benefits the organization and its interests, especially for customers of the Mother's Father's Cafe in Mimbaan, Panji District, Situbondo Regency. The purpose of this study is to analyze and test the influence of brand image and service quality on consulment satisfaction at the Cafe of the father of Mother Situbondo with consumer buying interest as an intervening variable. The population in this study were consumers at the Mother's Father's Cafe, , the sampling method is determined by probability sampling. Data analysis and hypothesis testing in research using sampling. Data analysis and hypothesis testing in the study using structural equation model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, Indicates that The image of the brand.